Marker of intrathecal immune activation for the evaluation of the IFN-β efficacy in relapsing-remitting multiple sclerosis - Koliada, Oleh; Myroshnychenko , Mykhailo; Vdovichenko, Nataly; Krestetska , Svitlana (Annals of Mechnikov’s Institute, 2021)
Multiple sclerosis is an autoimmune neurodegenerative disease of the central nervous system characterized by a violation of the integrity of the blood-brain barrier, an expansion of autoreactive lymphocyte clones specific to the membrane proteins of the nerve cells, and the formation of focal perivascular lymphocytic infiltrates. Interferon beta (IFN-β) is the first-line disease modifying drug in the treatment of relapsing-remitting multiple sclerosis (RRMS). However, clinical response varied among individuals, and about 20 % of IFN-β recipients haven’t improvement. Moreover, there are evidences suggestive of possible deleterious effect of IFN-β in some patients. The identification of biomarkers that can help in the early evaluation of the response to a patient’s treatment is necessary primarily for the individualized treatment of multiple sclerosis. In particular, cell-specific biomarkers of intra-inflammatory inflammation, which correlate with clinical manifestations of multiple sclerosis, can serve as informative indicators of the course of the disease. As a candidate marker of this type, the content of the soluble form of CD27 (sCD27) - a second type transmembrane glycoprotein, belonging to the TNF receptor (TNFRSF7) and expressing on the surface of cells of the lymphoid series, in cerebrospinal fluid is considered. It can be used as a cumulative indicator that correlates with the process of B-mediated antigen-specific T cell activation and is suitable for an objective assessment of the therapeutic effect of IFN-β in PPMS, starting from 6 months after initiation of therapy. Monitoring of CSF levels of sCD27, as treatment responsive marker of intrathecal immune activation, shows very promising results. Keywords: multiple sclerosis, biomarkers, IFN-β, CD27. DOI: 10.5281/zenodo.5761176